Flexural and direct tensile strength ratio for concrete unusual cross-sections - Fernandes Neto,José Anchiêta Damasceno (2023)
ABSTRACT The relationship between flexural and direct tensile strength (αfl ratio) has been explored in evaluations of the cracking moment for concrete structural elements. However, most results for αfl can be applied only for rectangular cross-sections. This manuscript addresses its obtaining for unusual cross-sections largely used in precast concrete elements. A theoretical analysis was performed in thirty-two different cross-sections regarding the compressive strength of concrete and the aggregate type used in the concrete composition. The results showed a smooth increase in αfl for higher strength concretes and lower elastic modulus aggregates. The theoretical procedure showed a good correlation with experimental data and prediction models and can be an interesting alternative for the obtaining of the αfl of unusual cross-sections.